Rancang Bangun Aerator Menggunakan Penggerak Motor Satu Fasa Dan Sistem Otomatisasi Berbasis Smart Relay - Arsaf, Abdul Gafar; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Oxigen in the water is obtained from 2 processes specifically the first is, photosynthesis by water plants and the second is aeration which included in the diffusion process. Aerator is a device that serves to produce oxygen through the diffusion process for the needs of living creatures in the water. Aerators themselves have several types, those are ; gravity aerator (gravity influence), surface aerator (surface), diffusier aerator (mixing), turbine aerator (windmill), and combination. The aerators which designed here are aerator type of turbine (turbine aerator) similar to the aerator used in the research area generally. The purpose in the making of an aerator with this automatic system is to simplify the management and also to reduce the operational costs of the ponds. Aerator is made using 2 pieces of waterwheel with each pin having the same 6 blades with a mill used in ponds at the research site. As the basis of the automation system, the aerator is a smart relay programmed with 2 input which are the light sensor and the sensor temperature parameters in the programming obtained from the results of research on dissolved oxygen levels in the water. From the results of the testing, when dissolved oxygen levels are relatively high in the range of 30mg/L light intensity > 100,000 lux and for temperature < 350 C. Then the results of the data retrieval is made into the input parameters in the programming. The results of the device testing shows that the performance which is as expected. Aerator can work well in increasing oxygen from 8mg/L – 14.4mg/L in 45 minutes and the controller work as programmed when dissolved oxygen level below standard with indication of light intensity < 40 lux and temperature >350 C.Keyword : Aerator, Dissolve Oxygen, Smart Relay